2009
DOI: 10.1007/s00404-008-0915-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Bishop score, body mass index and transvaginal cervical length in predicting the success of labor induction

Abstract: Body mass index and transvaginal cervical length were better predictors compared to the Bishop score in determining the success of labor induction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
3
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 28 publications
1
24
3
5
Order By: Relevance
“…Previous studies have shown that the rate of induced vaginal delivery is significantly higher in multiparous women compared to nulliparous women (4)(5)(6)(7) . In addition, some other studies have reported that no significant difference was found between the patients delivered by vaginal delivery and cesarean section (8,9) .…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Previous studies have shown that the rate of induced vaginal delivery is significantly higher in multiparous women compared to nulliparous women (4)(5)(6)(7) . In addition, some other studies have reported that no significant difference was found between the patients delivered by vaginal delivery and cesarean section (8,9) .…”
Section: Discussionmentioning
confidence: 95%
“…Cervical examination is of prime importance for elective labor induction (4)(5)(6) . The primary aim in this method is to predict whether labor will commence spontaneously.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…, propuseram um estudo para avaliar a eficácia da medida transvaginal do comprimento do colo uterino na predição (45) avaliaram o papel da ultrassonografia A idade gestacional foi calculada a partir da data da última menstruação (DUM), quando concordante com a ultrassonografia de primeiro trimestre; ou por este último quando a diferença era superior a sete dias.…”
Section: Introductionunclassified